ANALISIS KEBERADAAN PEDAGANG KAKI LIMA DI KORIDOR SUNGAI JAWI KOTA PONTIANAK - Nurhidayati, Ely (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2023)
Pontianak City has a role as a National Activity Center (PKN) in the West Kalimantan Province. So that makes Pontianak as a center of trade and services, as well as the entrance and exit of goods and people in the West Kalimantan region. The trade sector contributes 18% to the GRDP of Pontianak City compared to other sectors. Therefore, the trade sector becomes a business and job opportunity for the community. Generally, people's economic business actors engaged in the trading sector are street vendors (PKL). In this study, the distribution of street vendors in Pontianak City is divided into 4 (four) segments on the Jawi River corridor, Pontianak City. This raises aesthetic problems and compatibility with the function of the infrastructure facilities around the corridor. Meanwhile, the presence of street vendors also makes the Jawi River area a crucial area because of its role as Sub PPK III in the spatial structure of Pontianak City and its location on the side of the primary channel, namely the Jawi River. The government is also promoting Paret Berseh-Parit Cantek to maintain the sustainability and cleanliness of the rivers in Pontianak. This study aims to analyze the presence of street vendors in the corridor of the Jawi River, Pontianak City. The targets achieved are to identify the physical environment, social population, economic conditions, land use and distribution of street vendors, characteristics of street vendors, conditions and availability of infrastructure. In addition, it also analyzes the site footprint, location feasibility analysis, and capacity analysis. Keywords: Street Vendors, Jawi River, Pontianak